Traditional vs. sport-specific vertical jump tests: Reliability, validity, and relationship with the legs strength and sprint performance in adult and teen soccer and basketball players - Rodriguez-Rosell, D.; Mora-Custodio, R.; Franco-Márquez, F.; Yanez-Garcia, J. M.; González-Badillo, J. J. (The Journal of Strength and Conditioning Research, 2017)
The vertical jump is considered an essential motor skill in many team sports. Many protocols have been used to assess vertical jump ability. However, controversy regarding test selection still exists based on the reliability and specificity of the tests. The main aim of this study was to analyze the reliability and validity of 2 standardized (countermovement jump [CMJ] and Abalakov jump [AJ]) and 2 sport-specific (run-up with 2 [2-LEGS] or 1 leg [1-LEG] take-off jump) vertical jump tests, and their usefulness as predictors of sprint and strength performance for soccer (n = 127) and basketball (n = 59) players in 3 different categories (Under-15, Under-18, and Adults). Three attempts for each of the 4 jump tests were recorded. Twenty-meter sprint time and estimated 1 repetition maximum in full squat were also evaluated. All jump tests showed high intraclass correlation coefficients (0.969-0.995) and low coefficients of variation (1.54-4.82%), although 1-LEG was the jump test with the lowest absolute and relative reliability. All selected jump tests were significantly correlated (r = 0.580-0.983). Factor analysis resulted in the extraction of one principal component, which explained 82.90-95.79% of the variance of all jump tests. The 1-LEG test showed the lowest associations with sprint and strength performance. The results of this study suggest that CMJ and AJ are the most reliable tests for the estimation of explosive force in soccer and basketball players in different age categories.